2002
DOI: 10.1116/1.1518968
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic cleavage used in gold substrate production

Abstract: Articles you may be interested inNanoscale modifications of chalcogenide glasses using scanning tunneling microscopes J. Appl. Phys. 92, 5468 (2002); 10.1063/1.1513887 Modeling laser texturing of silicate glassAn improved method for the production of ultralarge flat and patterned gold surfaces for use in scanning probe studies using a procedure based on epitaxial gold growth on mica is described. The approach is superior in terms of simplicity and reliability without any loss of substrate quality. The gold sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…Mazurkiewicz and coworkers suggested that the pits were due to the imperfections on the template surface during evaporative deposition. [43] Our results on silicon are not supportive of this mechanism. Figure 3(f) is an AFM image of the template after stripping off the nonannealed gold layer.…”
Section: Resultscontrasting
confidence: 77%
“…Mazurkiewicz and coworkers suggested that the pits were due to the imperfections on the template surface during evaporative deposition. [43] Our results on silicon are not supportive of this mechanism. Figure 3(f) is an AFM image of the template after stripping off the nonannealed gold layer.…”
Section: Resultscontrasting
confidence: 77%
“…Large atomically-flat gold substrates were stripped from the mica template using procedure described by Shapter [25]. The basic idea is to use the first gold atomic layer which has been deposited directly on the mica rather than the top gold surface.…”
Section: Flat Goldmentioning
confidence: 99%
“…This feature raises the exciting possibility of one monolayer forming system being suitable for a large range of electrode materials for a diverse range of applications. Gold is important relative to carbon as it has a lower capacitance, and it can be produced very flat [35,36] or as a single crystal, and is compatible with microfabrication technologies.…”
Section: Introductionmentioning
confidence: 99%